Percurso diacrônico de completivas introduzidas por 'como' no português - Sousa, Gisele Cassia de [UNESP] (My University, 2013)
As a more extensive issue, this paper deals with the polysemy attested in all Romance languages between interrogative pronouns and subordination markers in complex sentences. It investigates, specifically, the behavior of objective complement clauses introduced by “como” (“how”) in constructions in which they occur as equivalent to the meaning of prototypical declarative complement clause introduced by the conjunction “que” (“that”). It analyzes complement clauses introduced by “como” and “que” occurring in representative Portuguese texts from the thirteenth to the twentieth centuries. The results of the comparative analysis between the two forms of clausal complement show that in archaic Portuguese “como” was used primarily to introduce complement clauses of factive verbs. When the complement clause is introduced by “como”, the content that is presupposed as true due to the meaning of matrix verb has reinforced this factuality. In the passage from the archaic to the modern period, there was a drastic decrease in the frequency of occurrences of complement clauses with “como”, which are replaced by the form of completive introduced by the conjunction “que” in the context of factual constructions. In contemporary Portuguese, this replacement is fully established. Complement clauses with “como” remain rare and limited to specific contexts in which “como” maintains its reinforcement function of factual meaning.

Este trabalho aborda, como temática mais ampla, a polissemia atestada em todas as línguas românicas entre pronomes interrogativos e marcadores de subordinação em senten- ças complexas. Investiga-se aqui, especificamente, o comportamento de orações completivas objetivas introduzidas por “como” que, nas construções em que aparecem, exibem significado equivalente ao de uma completiva declarativa prototípica, iniciada pela conjunção “que”. Analisam-se dados de completivas, tanto com “como” quanto com “que”, ocorrentes em textos representativos do português dos séculos XIII a XX. Os resultados da análise comparativa entre as duas formas de complemento oracional revelam que, no português arcaico, “como” era empregado preferencialmente para introduzir completivas declarativas de verbos factivos. Ao ser introduzido por “como”, alternativamente à conjunção “que”, o complemento oracional, cujo conteúdo é pressuposto verdadeiro por força do significado do verbo matriz, tem essa sua factualidade reforçada. Na passagem do período arcaico ao período moderno, observa-se queda drástica na frequência de ocorrências de oração completiva com “como” que, no contexto de construções factuais, é substituída pela forma de completiva introduzida pela conjunção “que”. No português contemporâneo, essa substituição mostra-se completamente implantada, permanecendo rara a forma de completiva com “como”, limitada a contextos específicos nos quais esse elemento introdutor mantém sua função de reforço de significado factual.
Diachronic path of complement clauses introduced by como in Portuguese
Keywords: orações completivas; complementizador interrogativo; factualidade; complement clauses; wh-complementizer; factuality